Beyond Trochenbrod : The Betty Gold Story - Gold, Betty, 1930-2014; Hodermarsky, Mark (Book collections on Project MUSE., 2014)
"Few are familiar with one of the Holocaust's most monstrous acts, the systematic murder of about 5,000 Jewish residents in a Nazioccupied Polish town, Trochenbrod, on August 11, 1942. Of the 33 who escaped death, only one person remains to describe these events--Betty Gold. Twelve-year-old Betty and her family hid inside a secret wall built by her father and, when it seemed safe, crept toward the forest, which became their home. In part one of Beyond Trochenbrod, Gold provides a brief history of Trochenbrod, the only all-Jewish town to exist outside of biblical Israel, and describes a series of cherished childhood experiences before the arrival of Soviet and, later, Nazi occupiers. Part two centers on the family's struggles against hunger, pain, despair, and the constant fear of being discovered while living in the forest. How the family survived against these and other threats is nothing short of miraculous. Their unlikely rescue, stay at a displaced persons camp, and journey to America are the subjects of part three. In the fourth and final part of her memoir, Gold recounts her difficult adjustment to her new home in Cleveland and discusses how her Trochenbrod experiences have transformed her life and the lives of others. Man's inhumanity is undeniable in Beyond Trochenbrod, but so is humanity's capacity to prevail in spite of unimaginable odds"--Publisher's description.